Permainan pasaran sebagai media untuk mengembangkan kompetensi interpersonal anak - Murti, Heru Astika Setya (Konsorsium Psikologi Ilmiah Nusantara, 2016)
Interpersonal competence is a necessary capability in establishing relationships with others. During childhood, this ability has been developed and can be stimulated through various methods. Play is one of several methods that can be used as it is related as an activity that is close to a child’s life. This play can be in the form of pretend play with the settings ‘Pasaran’. This study aims to determine the effect of ‘Pasaran’ play on children’s interpersonal competence. The method used in this research was quasi experiment using the untreated control group design with dependent pre-test and post-test samples. Two groups were used in this research, an experimental group (Pasaran play was given as the treatment) and the control group. Interpersonal competence is measured using Interpersonal Competence Scale based on the aspects by Buhrmester, dkk. (1998). The result showed that there is a difference in interpersonal competence between the experimental group and control group. The experimental group, the group that did Pasaran play, had interpersonal competence higher than the control group. It was concluded, Pasaran play can be used as a tool to develop interpersonal competence in children.